The association between anti-immigrant policies and perceived discrimination among Latinos in the US: A multilevel analysis. (December 2016) - Almeida, Joanna; Biello, Katie B.; Pedraza, Francisco; Wintner, Suzanne; Viruell-Fuentes, Edna
Abstract: Research has found a strong inverse association between discrimination and health and well-being. Most of these studies have been conducted among African-Americans, and have examined the relationship at the individual-level. To fill these gaps in knowledge we estimated the prevalence of perceived discrimination among a nationally representative sample of Latino adults in the US, and investigated the association between state-level anti-immigrant policies and perceived discrimination. We merged survey data with a state-level anti-immigrant policy index. First, we fit hierarchical logistic regression models to test the crude and adjusted association between anti-immigrant policies and perceived discrimination. Second, we specified cross-level interaction terms to test whether this association differed by relevant individual characteristics. Almost 70% of respondents reported discrimination (68.4%). More anti-immigrant policies were associated with higher levels of discrimination (OR=1.62, 95% CI 1.16, 2.24, p=0.01). The association between anti-immigrant policies and discrimination differed by place of origin (p=0.001) and was marginally moderated by generation status (p=0.124). Anti-immigrant policies stigmatize both foreign and US-born Latinos by creating a hostile social environment which affects their experiences of discrimination. These non-health policies can adversely affect Latino health, in part through exposure to discrimination, and may help explain health patterns among Latinos in the US. Highlights: Most studies of discrimination in the United States (US) have been conducted at the individual level and among African Americans. The effects of anti-immigrant policies such as Arizona's SB-1070, have largely gone unexamined by health and social science researchers. This study documents the prevalence of discrimination among a nationally representative sample of Latino adults in the US, and examines the association between state-level anti-immigrant policies and perceived discrimination. The prevalence of discrimination among Latinos in the US is similar to that found among African Americans. More anti-immigrant policies are associated with higher perception of discrimination.